Predictors Affecting the Level of Work Satisfaction in Relation to the Job Performance Among Secondary School Teachers in the Division of Zambales During SY 2020-2021 - Villanueva, Alma G.; Meer, Thelma Q. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The research aimed to determine the Predictors Affecting the Level of Work Satisfaction in Relation to the Work Performance Among Secondary School Teachers in the Division of Zambales During SY 20120-2021. The descriptive research design were used with survey questionnaire as the data gathering.The study was limited on predictors affecting the level of work performance as to teaching hours, salary/remuneration, school officials/administrators, peer/colleagues, student factor, work environment and community supports predictors respectively. The respondents of the study were Secondary Teachers in the Division of Zambales. The findings revealed that the teacher-respondent is a typical female in her early adulthood, married, Roman Catholic, Mathematics major, Teacher 1, BS degree with masteral units of education and had been teaching for almost a decade. The teacher-respondent agreed on the predictors affecting the level of work performance as to teaching hours, salary/remuneration, school officials/administrators, peer/colleagues, student factor, work environment factor and community support. The teachers were rated “Very Satisfactory” on their level of work performance. There was a significant difference on the assessment towards salary/remuneration when grouped according to civil status, religion and highest educational attainment; on school officials/administrators when grouped according to position/designation. There was significant difference on the assessment of the teacher-respondents towards predictors affecting the level of work satisfaction. There was no significant relationship between the work satisfaction predictors and the level of work performance as reflected in the IPCRF performance rating.